Tiktok As a Media Application for Improving the Student Speaking Skills - Gunawan; Taslim; Dewi Sartika (Decode: Jurnal Pendidikan Teknologi Informasi, 2023)
This research reports on the study of students' speaking ability through the use of the TikTok application. The problem of this research was the improvement of the students’ speaking accuracy and fluency through the use of the TikTok application at SMA Negeri 13 Bone. The purpose of the study was to determine students' ability to speak through the use of the TikTok application. The researcher used classroom action research (CAR), which was conducted in two cycles; each cycle consisted of four meetings. Thirty students in the eleventh grade at SMAN 13 Bone participated in this study The techniques for collecting data were observation and speaking tests. The research findings indicated that the application of the TikTok application was significant in improving the students’ speaking skills in terms of fluency and accuracy. It was proved by the mean score in the speaking ability for DT of 50.7, C1 of 65.79, and C2 of 77.69. So the improvement of the student's speaking ability from DT to C1 is 30.11%, DT to C2 is 52.96%, and CI to C2 is 18.08%. The researcher suggests that the use of media in language learning, particularly for speaking students, is absolutely essential. The TikTok media application is one that must be used. Students respond positively and enjoyably to the use of social media in the language learning process.